Molecular Detection of Some Virulence Genes in Pseudomonas aeruginosa Isolated from Chicken Embryos and Broilers with regard to Disinfectant Resistance - Hala S. Shahat (South Valley University, 2019)
Pseudomonas is a communal motif of environmental associated disease and causes a serious problem in poultry farms, so this study was deliberated to investigate the quandary of Pseudomonas species especially Pseudomonas aeruginosa (P. aeruginosa) which has multifarious virulence genes and plays a major role in poultry outbreaks. Also, it focuses the light on the problem of antimicrobial and disinfectant resistance. A total of 200 samples (100 from dead in shell chicken embryos and 100 from broilers at different ages) were collected from different hatcheries and farms in Luxor governorate, 40 isolates (20%) of Pseudomonas species were isolated and identified serologically as P.cepacia, P.fluorescens, P.putida, P.fragi and P.aeruginosa. PCR inveterate the existence of P.aeruginosa DNA in seven isolates by using 16SrDNA primers at 956bp. P.aeruginosa isolates have different virulence genes such as toxA, exoS, lasB, lasI and oprL gene with incidence rate 71.42% for each of them, except oprL was 100%. Also, Quaternary Ammonium Compounds resistant genes (QACs) were detected in P. aeruginosa isolates with incidence rate (14.28%) for each of qacAB and qacCD genes, while the qacED1 gene incidence was (100%). P. aeruginosa isolates showed an obstacle of antimicrobial resistance for different antimicrobials while most of these isolates cleared susceptibility for ciprofloxacin and norfloxacin. In conclusion, this work described the problem of P. aeruginosa as it proved a high virulence repertoire owned by the P. aeruginosa that confirming its pathogenicity for chicken embryos and broilers. Also, our study is fuelling the concern on disinfectant resistance problem and displaying the relation between QACs and antibiotic resistance. So, the deterrence of the Pseudomonas infection in the poultry housing becomes necessary by applying strict bio-security measures.